Emerging Soft Conductors for Bioelectronic Interfaces. (29th November 2019) - Gao, Dace; Parida, Kaushik; Lee, Pooi See
Abstract: Bidirectional interfacing between electrodes and biological systems has enabled diagnostics and therapeutics in modern medicine; however, the inherent dissimilarity between the soft, ion‐rich, dynamic biological tissues and the rigid, dry, static electronic systems hinders the establishment of effective and reliable bioelectronic interfaces. In the past decade, the scope of flexible/stretchable electronics has been broadened into bioelectronics owing to the need of implementation of various biocompatible soft conductors. Herein, the basic requirements for the construction of both epidermal and implantable bioelectronic interfaces utilizing soft materials are discussed, the most recent progress in the development of soft conductors, which are customized to interface with skin and other tissues, are summarized. An outlook into the remaining obstacles is provided and possible strategies to facilitate technological advances in bioelectronics are also outlined. Abstract : Soft and biocompatible electronic systems have started to revolutionize the future of health care. Herein, a full spectrum of recently developed soft conductors with target applications in epidermal and implantable bioelectronics is provided, the achievements being made so far are summarized, and the challenges to be solved to further advance the development of next‐generation bioelectronic interfaces are addressed.